Pengaruh Media Menempel Gambar terhadap Pengetahuan dan Keterampilan Cuci Tangan Pakai Sabun pada Anak Usia Dini - Karisa Ginatania Auliani; Emelia Tonapa; Desie Rahmawati (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Young children can be said to be a group at risk to disease-causing germs, such as those that cause diarrhea. Most cases of diarrhea may be avoided by doing hand washing with soap (HWWS). The results of a preliminary study at Keledang Kindergarten showed that seven children had experienced diarrhea in the past month and had not been practicing proper handwashing with soap. This study is intended to analyze the impact of health education using sticker media on the knowledge along with capabilities of handwashing with soap among young children at Keledang Kindergarten in Samarinda. This study implemented a pre-experimental design with a one-group pretest-posttest design. The study sample included children in Kindergarten Class B at Keledang Kindergarten in Samarinda, totaling 66 respondents selected using purposive sampling. The variables included knowledge and skills related to hand washing with soap. Data were collected using picture cards and checklists. Data analysis was completed using the Wilcoxon test. Before the intervention, 100% of the respondents had insufficient knowledge and were unskilled. After the intervention, knowledge improved to the good category (77,3%) and skills improved to highly skilled (87,9%). The Wilcoxon test yielded a p-value of 0,000 (p < 0,05). Health education using sticker media materials had a significant effect on knowledge and skills related to HWWS among early childhood students at Keledang Kindergarten in Samarinda; finally, this method is highly suggested as a solution for health education tool for young children.